Confluence of Leadership Dynamics, Organizational Politics, and Faculty Morale and Its Impact in Higher Education: An Exploratory Case Study - N. Fathima Thabassum (Journal of Education for Sustainable Development Studies, 2026)
This exploratory qualitative case study examines how leadership dynamics and organizational politics shape faculty morale and institutional readiness for Education for Sustainable Development (ESD) in a mid-sized self-financing college in South India. It analyses how organizational politics influence decision-making, role allocation, and administrative behavior, and how these processes affect faculty participation and institutional culture. The study further derives implications for leadership development and governance reform aimed at enhancing ESD readiness. Drawing on French and Raven’s Bases of Power (1959), McGregor’s Theory X–Y (1960), Schein’s model of organizational culture (1985), and contemporary ESD literature, the study triangulates reflective observations, semi-structured faculty interactions (n = 12), and institutional document analysis (2020–2024). Thematic analysis identified five core themes: administrative centralization, selective delegation, sponsorship politics, cultural inconsistency, and declining faculty engagement. Centralized decision-making and opaque delegation practices reduced faculty autonomy, generated role ambiguity, and redirected effort toward political navigation rather than academic innovation. Conversely, transparent communication, participative governance, and recognition of expert competence were associated with higher levels of trust, engagement, and capacity to integrate sustainability into teaching and institutional practice. The findings suggest that ethical, competence-based, and participative leadership is essential not only for sustaining faculty morale but also for enabling institutional transformation toward ESD. Accordingly, recommendations include governance reform, leadership capacity building, transparent administrative processes, and mechanisms for monitoring organizational climate, which function synergistically to counteract politicized work environments, reinforce ethical and transformational leadership, and strengthen organizational commitment, academic productivity, and the long-term sustainability of higher education institutions.